Combined atrial fibrillation ablation and left atrial appendage closure: long-term follow-up from a large multicentre registry. Issue 11 (13th March 2018) - Wintgens, Lisette; Romanov, Aleksandr; Phillips, Karen; Ballesteros, Gabriel; Swaans, Martin; Folkeringa, Richard; Garcia-Bolao, Ignacio; Pokushalov, Evgeny; Boersma, Lucas
Abstract: Aims: Long-term freedom from atrial fibrillation (AF) after catheter ablation (CA) and consequently the potential for stroke reduction remain unpredictable. Percutaneous left atrial appendage closure (LAAC) is an effective mechanical alternative to oral anticoagulation (OAC) for stroke prevention in AF patients. This study aims to evaluate long-term clinical results of combined CA and LAAC in one single procedure. Methods and results: Patients with non-valvular AF who underwent combined CA and LAAC procedure were included in the retrospective compilation of independent prospective general LAAC registries at the individual centres. Transoesophageal echocardiography (TOE) was used to evaluate device position and LAA sealing. Between 2009 and 2015, 349 patients with AF (58% male, age 63.1 ± 8.2 years; score for stroke prediction in AF patients (CHA2 DS2 -VASc) 3.0; score for major bleeding in patients on anticoagulation (HAS-BLED) 3.0; 56% paroxysmal AF) were included. Indications for LAAC included previous stroke (38%), history of bleeding (22%), and physician/patient preference (29%). Periprocedural complications up to 30 days included pericardial effusion (1.5%) and one minor stroke (0.3%) but no death. After 6 weeks, TOE showed successful sealing of the LAA in 98.9%. After 35 months of follow-up, 51% of patients had AF recurrence. A total of nine ischaemic strokes were recorded, resulting in an annualized stroke rate of 0.9% compared to an expected stroke rate of 3.2% without anticoagulation and combined treatment. Conclusion: This large pooled multicentre analysis of five prospective registries shows that combining CA and LAAC is feasible, safe, and successful. Long-term follow-up shows greatly reduced stroke and bleeding rates despite recurrence of AF in more than half of the patients.